BIMBINGAN TEKNIS (BIMTEK) AWAL TAHUN AKADEMIK 2024/2025: PENYUSUNAN PERANGKAT AJAR KURIKULUM MERDEKA DI UPTD SDN BATUPLAT 2 KUPANG - Fointuna, Daniel Williams; Koroh, Taty Rosiana; Bulu, Vera Rosalina; Lehan, Andriyani Afliyanti Dua (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
A technical guidance of creating teaching materials based on Merdeka curriculum framework was conducted in the beginning of academic year 2024/2025 from August 1 – 3, 2024, in UPTD SDN Batuplat 2 Kupang. The community service activity was participated by 29 participants of teachers and education personnels of UPTD SDN Batuplat 2 Kupang. This activity was carried out using training and assisting method. Qualitatively, the final survey showed that all participants obtained meaningful knowledge, understanding, and skill to create teaching materials incorporating differentiated learning. The participants were able to integrate digital learning media in the teaching materials they had created. Besides, quantitatively, the final survey indicated that as many as 26 teachers could produce differentiated learning modules according to classes and levels where they teach, 5 teachers and education personnels could produce HTML and android-based application for AKM simulation using I spring suite. Moreover, 9 teachers and education personnels could produce interactive teaching materials, quizzes, and games using web-based application, such as genially, educaplay, and wordwall.